KAJIAN NILAI-NILAI KARAKTER DALAM PEMBELAJARAN MATEMATIKA SEKOLAH MELALUI PENDEKATAN ANALOGI [A STUDY OF CHARACTER VALUES IN SCHOOL MATHEMATICS LEARNING THROUGH AN ANALOGY APPROACH] - Seleky, Jacob S (JOHME: Journal of Holistic Mathematics Education, 2021)
School math learning is part of the educational process that provides students with a mathematics learning experience through a planned set of activities to achieve established goals. The goal of learning mathematics in schools in Indonesia is oriented towards achieving a balance between the cognitive, affective, and psychomotor domains. In fact, learning mathematics in schools in Indonesia so far has focused on efforts to achieve high scores from the cognitive domain. But along with the development and change of curriculum, affective and psychomotor domains are receiving more priority to develop. In this paper, the author wants to examine the affective domain by conducting a study of character values in school mathematics learning through an analogy approach. This paper aims to contribute ideas related to the development of affective domains in learning mathematics through the study conducted. The research method used is a literature study. While the strategy for conducting the study is an analogical approach that is associated with the understanding of quantitative and qualitative relationships. Based on the results, it is evident that in school mathematics learning implied character values are learned. The author hopes that this study will be useful to math teachers in developing the affective domain of math learning in schools. The implication is that the goal of learning mathematics, namely the balance between the cognitive, affective, and psychomotor domains, can be achieved.BAHASA INDONESIA ABSTRACT: Pembelajaran matematika sekolah adalah bagian dari proses pendidikan yang memberikan pengalaman belajar matematika kepada siswa melalui serangkaian kegiatan yang terencana untuk mencapai tujuan yang telah ditetapkan. Tujuan pembelajaran matematika sekolah di Indonesia berorientasi untuk mewujudkan keseimbangan antara domain kognitif, afektif, dan psikomotor. Pada kenyataannya pembelajaran matematika sekolah di Indonesia selama ini menitikberatkan pada upaya pencapaian nilai yang tinggi dari domain kognitif. Tetapi bersamaan dengan pengembangan dan pergantian kurikulum, domain afektif dan psikomotor mendapat prioritas untuk dikembangkan. Oleh karena itu, dalam paper ini penulis ingin mengembangkan domain afektif dengan melakukan kajian nilai-nilai karakter dalam pembelajaran matematika sekolah melalui pendekatan analogi. Penulisan paper ini bertujuan untuk memberikan kontribusi pemikiran terkait pengembangan domain afektif dalam pembelajaran matematika. Metode penelitian yang digunakan adalah studi literatur. Sedangkan strategi melakukan kajian adalah pendekatan analogi yang dikaitkan dengan pemahaman hubungan kuantitatif dan kualitatif. Berdasarkan hasilnya dapat diketahui bahwa didalam pembelajaran matematika sekolah terdapat nilai-nilai karakter yang tersirat untuk dipelajari. Harapan penulis, kajian ini bermanfaat untuk guru matematika dalam mengembangkan domain afektif pembelajaran matematika di sekolah. Implikasinya tujuan pembelajaran matematika yaitu keseimbangan antara domain kognitif, afektif dan psikomotor dapat tercapai.